Detection of Islet Cell Immune Reactivity with Low Glycemic Index Foods: Is This a Concern for Type 1 Diabetes? - Datis Kharrazian; Martha Herbert; Aristo Vojdani (Journal of Diabetes Research)
Dietary management of autoimmune diabetes includes low glycemic foods classified from the glycemic index, but it does not consider the role that immunoreactive foods may play with the immunological etiology of the disease. We measured the reactivity of either monoclonal or polyclonal affinity-purified antibodies to insulin, insulin receptor alpha, insulin receptor beta, zinc transporter 8 (ZnT8), tyrosine phosphatase-based islet antigen 2 (IA2), and glutamic acid decarboxylase (GAD) 65 and 67 against 204 dietary proteins that are commonly consumed. Dietary protein determinants included unmodified (raw) and modified (cooked and roasted) foods, herbs, spices, food gums, brewed beverages, and additives. There was no immune reactivity between insulin or insulin receptor beta and dietary proteins. However, we identified strong to moderate immunological reactivity with antibodies against insulin receptor alpha, ZnT8, IA2, GAD-65, and GAD-67 with several dietary proteins. We also identified 49 dietary proteins found in foods classified as low glycemic foods with immune reactivity to autoimmune target sites. Laboratory analysis of immunological cross-reactivity between pancreas target sites and dietary proteins is the initial step necessary in determining whether dietary proteins may play a potential immunoreactive role in autoimmune diabetes.